CALIFORNIANS AGAINST UNFAIR TAX INCREASES SAYS TOBACCO TAX INITIATIVE WOULD CAUSE CRIME, PENALIZE POOR (Tufts Archival Research Center, 2007)
Missing Page(s); Californians Against Unfair Tax Increases (CAUTI) press release opposing the tobacco tax initiative. Argues tax would result in increased crime, unfair taxation of low wage workers, and large financial benefits for doctors. Discusses position of the proposed tax. Mentions CAUTI press briefings.